Moral foundations are not moral propositions. (2019) - Haas, Daniel
Abstract: Joshua May responds to skepticism about moral knowledge via appeal to empirical work on moral foundations. I demonstrate that the moral foundations literature is not able to do the work May needs. It demonstrates shared moral cognition, not shared moral judgment, and therefore, May's attempt to defeat general skepticism fails.